ANALYSIS OF HUMAN CAPITAL, SOCIAL CAPITAL, ORGANIZATIONAL CAPITAL ON EMPLOYEE PERFORMANCE AT THE REGIONAL SERVICE AGENCY OF MALUKU PROVINCE - Junus Kwelju; Anthonio Johan Latuihamallo (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to analyze the effect of human capital, social capital, and organizational capital on employee performance. The approach used is a survey. The population is all Maluku Province BKD employees totaling 64 people. Sample selection is done by simple random sampling of 30 employees. Data were analyzed using multiple linear regression. The results showed that human capital, social capital and organizational capital had a positive and significant effect partially and simultaneously on employee performance and human capital was the most dominant influence on employee performance.